Metformin bicarbonate-mediated efficient RNAi for precise targeting of TP53 deficiency in colon and rectal cancers. (April 2022) - Xu, Jiangsheng; Liu, Yunhua; Liu, Sheng; Ou, Wenquan; White, Alisa; Stewart, Samantha; Tkaczuk, Katherine H.R.; Ellis, Lee M.; Wan, Jun; Lu, Xiongbin; He, Xiaoming
Highlights: Metformin bicarbonate (MetC) is synthesized to produce gas under acidic condition. MetC-based nanoparticle is synthesized to generate "bomb" effect in late endosome. The "bomb" effect enables endosomal escape of siRNA for effective RNAi in cytosol. MetC has a similar anticancer effect to the commonly used metformin hydrochloride. Colon and rectal cancers may not be simply combined as colorectal cancer for study. Graphical Abstract: Metformin bicarbonate is synthesized to develop pH-responsive nanoparticles with the unique "bomb" effect for cytosol-specific delivery of siRNA to precisely target POLR2A, an essential gene for cell survival and proliferation that is always co-deleted with the tumor suppressor gene TP53 in both colon and rectal cancers. This greatly augments the therapeutic efficacy of POLR2A siRNA for these cancers harboring TP53 deficiency. ga1 Abstract: Colon and rectal cancers are the leading causes of cancer-related deaths in the United States and effective targeted therapies are in need for treating them. Our genomic analyses show hemizygous deletion of TP53, an important tumor suppressor gene, is highly frequent in both cancers, and the 5-year survival of patients with the more prevalent colon cancer is significantly reduced in the patients with the cancer harboring such deletion, although such reduction is not observed for rectal cancer. Unfortunately, direct targeting TP53 has been unsuccessful for cancer therapy. Interestingly, POLR2A, a gene essential for cell survival and proliferation, is almost always deleted together with TP53 in colon and rectal cancers . Therefore, RNA interference (RNAi) with small interfering RNAs (siRNAs) to precisely target/inhibit POLR2A may be an effective strategy for selectively killing cancer cells with TP53 deficiency. However, the difficulty of delivering siRNAs specifically into the cytosol where they perform their function, is a major barrier for siRNA-based therapies. Here, metformin bicarbonate (MetC) is synthesized to develop pH-responsive MetC-nanoparticles with a unique "bomb" effect for effective cytosolic delivery of POLR2A siRNA, which greatly facilitates its endo/lysosomal escape into the cytosol and augments its therapeutic efficacy of cancer harboring TP53 deficiency. Moreover, the MetC-based nanoparticles without functional siRNA show notable therapeutic effect with no evident systemic toxicity or immunogenicity.